The Influence of Transformational Leadership, Interpersonal Communication, and Organizational Commitment of Public Service Quality in BNP2TKI - Abdul - Ghofar; Wibowo; Burhanuddin Tola (Program Studi S3 Ilmu Manajemen, 2018)
ABSTRACT The purpose of this research is to measure direct and indirect influence of transformational leadership, interpersonal communication, and organizational commitment for public service quality in BNP2TKI. This study used survey method, and included in quantitative research. Sample is calculated using Slovin method, is set minimum sample for 140 people, taken by systematic random sampling. Method of data collection by dissemination research instrumens to selected respondents. Method of data analysis using path analysis. The result of the research shows that there are positive direct influence of transformational leadership, interpersonal communication and organizational commitment toward the quality of public service in BNP2TKI. Transformational leadership and interpersonal communication has the positive direct influence for organizational commitment. Transformational leadership has the positive direct influence for interpersonal communication. Transformational leadership has the biggest direct influence for the quality of public service of BNP2TKI. Keywords: The Quality of Public Service, Transformational Leadership, Interpersonal Communication, Organizational Commitment.